The Relationship between Pre Discharge Left Ventricle Diastolic Dysfunction and 30 days And 6 Months Rehospitalization in Patients with Heart Failure with Reduced Ejection Fraction (HFrEF) at Haji Adam Malik General Hospital Medan - Khaidirman, Sophia Khairina; Mukhtar, Zulfikri; Sarastri, Yuke; Ketaren, Andre Pasha; Raynaldo, Abdul Halim; Andra, Cut Aryfa (Journal of Society Medicine, 2023)
Introduction: Heart failure (HF) is a complex clinal manifestation that cause abnormality of structural and/or functional of the heart. HF is due to diastolic dysfunction and systolic dysfunction of the left ventricle (LV). The aim of this study is to assess the relationship between grading of pre-discharge LV diastolic dysfunction and readmission at 30 days post discharge and 6 months post discharge. Method: This is a cohort retrospective study in HFrEF patients which are treated at Pusat Jantung Terpadu RSUP H. Adam Malik Medan on January 2021 until December 2021. Pre discharge echocardiography has been done to assess LV diastolic dysfunction and the we do the follow up of readmission at 30 days and 6 months by phone. Results: From 93 patients, there are 40 patients (43%) with grade I LV diastolic dysfunction, 22 patients (23,7%) with grade II LV diastolic dysfunction and 31 patients (33,3%) with grade III LV diastolic dysfunction. There are 34 patients (26,6%) with readmission at 30 days and 21 patients (26,6%) readmission at 6 months. There is a significant relationship between grading of pre-discharge LV diastolic dysfunction and readmission at 30 days post discharge (p value 0,000), but not at 6 months post discharge (p value 1,000). Conclusion: Grading of pre-discharge LV diastolic dysfunction on HFrEF patient is correlated with readmission at 30 days post discharge.